Fast electrical diagnostics and dispersion relation for ion density determination in an atmospheric pressure argon plasma. (7th December 2020) - Gerling, T; Wilke, C; Becker, M M
Abstract: Investigations of an atmospheric pressure gas discharge in argon focusing on the experimental measurement of the ion density is presented. The suggested diagnostic method combines the evaluation of weak and erratically occurring oscillations of the current signal with the solution of the dispersion relation for the dominant ion species. The considered dispersion relation contains the contribution of electron and ion movement as well as collisions of ions with the neutral background gas. The solution is performed considering temporal decay and spatial damping, respectively, and shows the existence of an ion acoustic wave (IAW) despite atmospheric pressure conditions. A parameter variation when using the dispersion relation reveals a limited range of existence of an IAW depending strongly on the ion density and correlates with experimentally acquired values of the molecular argon ion density of about 10 12 cm −3 . Furthermore, the combination of the experimental investigations and the solution of the dispersion relation provides access to the molecular argon ion—neutral argon collision frequency with values of about 2×10 7  Hz and 6×10 7  Hz, respectively.